2009
DOI: 10.2139/ssrn.1392630
|View full text |Cite
|
Sign up to set email alerts
|

Poll Workers, Election Administration, and the Problem of Implicit Bias

Abstract: Racial bias in election administration-more specifically, in the interaction between poll workers and voters at a polling place on election day-may be implicit, or unconscious. Indeed, the operation of a polling place may present an "optimal" setting for unconscious racial bias. Poll workers sometimes have legal discretion to decide whether or not a prospective voter gets to cast a ballot, and they operate in an environment where they may have to make quick decisions, based on little information, with few conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Furthermore, there is some research that finds that voter confidence can influence turnout (Alvarez, Hall, and Llewellyn 2008;Kerevel 2009), suggesting that pollworker discretion can have substantial consequences for voters. Second, previous research has suggested certain groups of voters may be disproportionately impacted by poll-worker discretion in the application of voter identification laws (Ansolabehere 2009;Cobb et al 2012;Page and Pitts 2009). If poll workers can use their discretion to discriminate against particular voters, as feared by Page and Pitts (2009), policy makers may wish to consider election reforms that restrict the ability of poll workers to use their own discretion in deciding what type of identification to accept from voters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, there is some research that finds that voter confidence can influence turnout (Alvarez, Hall, and Llewellyn 2008;Kerevel 2009), suggesting that pollworker discretion can have substantial consequences for voters. Second, previous research has suggested certain groups of voters may be disproportionately impacted by poll-worker discretion in the application of voter identification laws (Ansolabehere 2009;Cobb et al 2012;Page and Pitts 2009). If poll workers can use their discretion to discriminate against particular voters, as feared by Page and Pitts (2009), policy makers may wish to consider election reforms that restrict the ability of poll workers to use their own discretion in deciding what type of identification to accept from voters.…”
Section: Discussionmentioning
confidence: 99%
“…Second, previous research has suggested certain groups of voters may be disproportionately impacted by poll-worker discretion in the application of voter identification laws (Ansolabehere 2009;Cobb et al 2012;Page and Pitts 2009). If poll workers can use their discretion to discriminate against particular voters, as feared by Page and Pitts (2009), policy makers may wish to consider election reforms that restrict the ability of poll workers to use their own discretion in deciding what type of identification to accept from voters. Clear guidelines and procedures that prevent poll workers from using their discretion are likely the best way for this to be achieved.…”
Section: Discussionmentioning
confidence: 99%
“…In courtrooms, expert witnesses invoke IAT research to support the proposition that unconscious bias is a pervasive cause of employment discrimination (Greenwald, 2006; Scheck, 2004). Law professors (e.g., Kang, 2005; Page & Pitts, 2009; Shin, 2010) and sitting federal judges (Bennett, 2010) cite IAT research conclusions as grounds for changing laws. Indeed, the National Center for State Courts and the American Bar Association have launched programs to educate judges, lawyers, and court administrators on the dangers of implicit bias in the legal system, and many of the lessons in these programs are drawn directly from the IAT literature (Drummond, 2011; Irwin & Real, 2010).…”
mentioning
confidence: 99%
“…What explains our results? Following Page and Pitts (2009), we hypothesize that a plausible explanation is unconscious 15 stereotyping or assumptions on the part of poll workers, the street level bureaucrats (Lipsky, 1980) charged with administering election laws. Rarely are poll workers even considered an arm of the state, or ''as provider[s] of a service, even though they clearly operate as extensions of a government agency and do provide a service to the voter'' (Hall et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…As Page and Pitts (2009) suggest, such trying circumstances provide a setting in which subconscious assumptions regarding race and the need for additional verification of eligibility may operate.…”
Section: Discussionmentioning
confidence: 99%